(untitled) (Jurnal Adabiya, 2020)
Penan Jeb tradition is a unique tradition of Gayo Lues people, this tradition is commonly held along together with others religious ritual such as Eid Al Adha, mauled (birth of the prophet) and aqiqah (ritual of new-born), as a tradition that has been regulated from generation to generation, Penan Jeb has developed new form and pattern along the way, for instance the declining of ritual held in every household and the adding of modern snack to its menu which normally consist of traditional cookies, this study aimed to find an answer to some questions of historical background of Penan Jeb tradition, the processing of ritual Penan Jeb, its development and its significance meanings, this study uses qualitative method of analytical description, the results of study show that the reason behind the declining of Penan Jeb proceeding is due to practical factor, before, Penan Jeb was held in every household, now people prepare the food and cookies and bring it to the pesantren (Islamic boarding school) to be held in one centralized place.